“Teachers' Emotional Labor” Publications in Web of Science: A Bibliometric Analysis - Aihui Wu; Rining Wei (Frontiers in Psychology, 2022)
One of the indicators that symbolize the success of an academic field is its academic publications in well-established citation indices. This article first explored the bibliometric characteristics of publications on “teachers' emotional labor” (TEL) in the Social Sciences Citation Index (SSCI) and the Arts & Humanities Citation Index (A&HCI), two prestigious citation indices available in the Web of Science (WoS). Search with the term “teacher emotional labor” retrieved 173 publications that included this term in their titles, abstracts, or keywords in the WoS database between 1900 and 2020. The bibliometric characteristics pertaining to numbers of publications, document types, research categories, research areas, authors, journals, universities, and countries were reported. Then, CiteSpace was utilized to visualize TEL research and to obtain insights into its research focuses and its future directions. The findings will contribute to TEL research by informing scholars in the fields of L2 research and psychology and others.